Analysis of Filter System Study to Maintain Liquid Quality Cooler for Conventional Lathe Machines - Basri, Filza Izzati; Ibrahim, Badaruddin; Shaari, Norlida (Research and Innovation in Technical and Vocational Education and Training, 2024)
This study aimed to improve the coolant filter system to maintain its quality and longevity in the machining process. It tested the cooling liquid's quality against the filter system and compared it with a mesh wire filter. The analysis method involved five phases: identifying and defining the problem, designing the experimental procedure, conducting the experiment, collecting data, analyzing experimental data, and proposing a solution. The study found a gap in value differences between viscosity, concentration, and weight of scroll fragments. The recommendation for future research is to apply the study to CNC machines and understand each analysis to ensure accurate data collection. The study aims to determine the need to replace the filter in the cooling liquid system to ensure its quality efficiency and long-term use as a cooling agent.